2006
DOI: 10.1002/ejoc.200600664
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole‐pyrrolidine/H+ (BIP/H+), a Highly Reactive Organocatalyst for Asymmetric Processes

Abstract: A new chiral benzimidazole‐pyrrolidine has been devised, which exhibits excellent activities in aminocatalyzed aldol reactions, leading to aldol products in high yields and enantioselectivities in the presence of an equimolar amount of a Brönsted acid. This organocatalyst has demonstrated remarkable reactivities in aldol processes even with equimolar amounts of aldehyde and ketone in THF. A discussion of the role of the Brönsted acid as a co‐catalyst is provided along with some applications of this new class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…[23] Robinson annulation of 11 to 9 was accomplished by optimizing the Tu/Zhang conditions. [23c] At the onset of the study, we found that treatment of 11 with 30% D -prolinamide/PPTS at 80 °C over 12 h afforded 9 in 74% yield and 70% ee .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Robinson annulation of 11 to 9 was accomplished by optimizing the Tu/Zhang conditions. [23c] At the onset of the study, we found that treatment of 11 with 30% D -prolinamide/PPTS at 80 °C over 12 h afforded 9 in 74% yield and 70% ee .…”
Section: Resultsmentioning
confidence: 99%
“…[23] Robinson annulation of 11 to 9 was accomplished by optimizing the Tu/Zhang conditions. [23c] At the onset of the study, we found that treatment of 11 with 30% D -prolinamide/PPTS at 80 °C over 12 h afforded 9 in 74% yield and 70% ee . On the other hand, at room temperature this reaction needed up to 60 days to completely consume the starting material thus yielding enantiomerically pure (−)- 9 (> 99% ee ).…”
Section: Resultsmentioning
confidence: 99%
“…Benzimidazole-pyrrolidine 42 ( Figure 4) in combination with trifluoroacetic acetic (10-20 mol%) was also applied as catalysts for this transformation in dicloromethane at room temperature affording the aminated products 41 in lower yields and enantioselectivities (65-92%, ee 66-71%) [38]. Aryl ketones can be also aminated using as catalyst the amine 43 derived from cinchona alkaloids (Figure 4, 20 mol%) [39].…”
Section: Methodsmentioning
confidence: 99%
“…Our synthetic approach departed from commercially available diketone 12 that was converted to compound 13 [xii] in two steps and 63% yield (Scheme 2). D-prolinamide/PPTS-catalyzed [12c] optimized asymmetric aldol condensation of 13 produced optically enriched diketone 11 in 74% yield (> 90% ee ).…”
mentioning
confidence: 99%
“…D-prolinamide/PPTS-catalyzed [12c] optimized asymmetric aldol condensation of 13 produced optically enriched diketone 11 in 74% yield (> 90% ee ). Regio- and stereoselective reduction of the more electrophilic C1 carbonyl group of 11 followed by selected silylation of the resulting alcohol using NH 4 NO 3 /TBS-Cl conditions [11d, xiii] produced compound 14 (2 steps, 92% yield).…”
mentioning
confidence: 99%